INTERNAL COMMUNICATION AND TEAMWORK AS DETERMINANTS OF EMPLOYEE PRODUCTIVITY IN VIDEO STREAMING FIRMS - Priyono, Agung; Rezika Lubis, Siti Raisa; Azhar, Muhammad Akmal; WS, Paidi (Journal of Management and Leadership, 2025)
After more than three years of fighting together to face the Covid-19 pandemic, the Indonesian government finally decided to revoke the status of the pandemic to endemic in June 2023. The habit during a pandemic where people are required to stay at home continues in the endemic era. An activity that many people still do is use applications via computers, laptops or smartphones to watch on video streaming platforms. As reported by Populix.co, in 2022, 84% of Indonesians subscribe to video streaming applications because they can be watched at any time, 77% have a large choice of films and 74% are looking for entertainment. Based on this trend, many video streaming companies have emerged in Indonesia, one of which is PT Vidio Dot Com (Vidio) which offers many types of viewing for its users. Data from the telecommunications market segment (telco 2022), Vidio is recorded as having the first highest number of 27.7 million active users in Indonesia, Netflix 11.3 million, Viu 10.4 million, and Disney+ 2.4 million. Seeing the large number of Vidio users, companies must pay attention to important factors so as not to lose customers, one of which is human resource management. Without a well-functioning HRM function, employee productivity will not be optimal. This research aims to determine the effect of internal communication and teamwork on employee productivity at Vidio. This research used quantitative methods with random sampling techniques and numbered 86 respondents. The research results show that internal communication has a positive and significant effect on employee productivity, and teamwork has a positive and significant effect on employee productivity.